Performance evaluation of bromelain extraction from pineapple rhizome using in-house freeze dryer - Theansuwan, Wasan; Kumnorkaew, Theerawat; Suksuntornsiri, Pawinee (International Journal of Innovative Research and Scientific Studies, 2025)
This study introduces an innovative approach for extracting bromelain from pineapple rhizomes using a custom-designed in-house freeze dryer. Equipped with a six-tray layout, the system efficiently processes up to 3 kg of wet bromelain. We employed an air-blast mechanism for rapid initial freezing, followed by a vacuum freeze-drying process, with a key innovation being the deactivation of the cooling fan post-freezing to facilitate efficient ice sublimation. Throughout the entire drying process, the operational temperature and pressure conditions within the freeze dryer's refrigeration system were thoroughly recorded and presented, a crucial step for monitoring and verifying the machine's performance and efficiency. The freeze-drying procedure encompassed three distinct phases: rapid initial freezing, primary drying with pressure reduction and gradual heating, and secondary drying for further moisture removal via increased temperature. Comparative analysis with lab-scale dryers demonstrated that the bromelain extracted using our in-house system retained enzymatic activity levels comparable to conventional methods, validating the efficacy of our machine for consistent, high-quality extraction. This study confirms the effectiveness of our innovative freeze-drying method and provides valuable insights into operational parameters like temperature progression and power consumption, significantly contributing to the broader understanding of freeze-drying techniques in enzyme extraction.